Implementation of Andragogical Principles in Developing Life Skills of Santriwati in Islamic Boarding Schools in the Modern Era - Yoshehira, Orien; Arbarini, Mintarsih; Siswanto, Yudi (Fitrah: Journal of Islamic Education, 2025)
The principles of andragogy have not been widely applied in adult learning within Islamic boarding schools, despite their potential to foster learner autonomy and enhance the relevance of instruction. This study aims to describe the implementation of andragogical principles in developing the life skills of santriwati (female students) at Pondok Pesantren Al-Asror. Employing a descriptive qualitative method, the study involved three santriwati, one ustazah (female teacher), and one administrator as participants. Data were collected through non-participant observation, semi-structured interviews, and document analysis, with data validity ensured through source and technique triangulation. Data analysis consisted of data collection, reduction, presentation, and conclusion drawing. The findings indicate that the application of andragogical principles is reflected in the santriwati’s development of self-concept toward independence, the use of learning experiences to enhance relevance, the alignment of training with learners’ readiness, and the orientation of learning toward spiritual independence and practical skills. Challenges include technological limitations and hierarchical cultural norms that restrict autonomy. The study implies the need for innovation in learning systems and the use of technology to make the application of andragogical principles in Islamic boarding schools more effective and adaptive to contemporary developments.